Perancangan Sistem Informasi Akademis Perguruan Tinggi\ Menggunakan Diagram Use Case dan Rich Picture - Iskandar, Karto (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This research is a continuation of previous research, which is a development of academic information systems for higher education with database reporting of EPSBED to DIKTI. Researchers will continue to develop the design using use case diagrams and rich picture diagrams. The design is useful to help the team of developers in building the application especially in coding process. The method used is studying the results of previous research then developing the design of use case diagrams and finally making the rich picture diagrams. The results of this research is a process design of a university in use case diagrams and rich picture diagrams. This research found that an academic information systems can be designed with use case diagrams and rich picture diagrams to facilitate coding process. This design is expected to be developed into a ready-use application that can be utilized in universities.